2010
DOI: 10.1007/s11626-010-9282-6
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cell lines isolation, cultivation, and characterization

Abstract: A large number of human embryonic stem cell (hESC) lines have been derived worldwide since the first hESC line establishment in 1998. Despite many common characteristics, most important of which is the pluripotency, hESC lines vary significantly in their transcriptional profiles, genetic, and epigenetic state. These differences may arise both from individual genetics of the cell lines and from variations in their handling such as isolation and cultivation. In order to minimize the latter differences, the stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…Matrigel matrix together with mTeSR1 medium is widely used in different laboratories, and several research groups have reported this culture condition to maintain the undifferentiated growth of hPSCs [8], [9], [26], [27], [38]. In these studies, the pluripotency of hPSCs was confirmed by teratoma and EB formation and analysis of the expression of markers specific to all three germ layers present in these structures.…”
Section: Discussionmentioning
confidence: 99%
“…Matrigel matrix together with mTeSR1 medium is widely used in different laboratories, and several research groups have reported this culture condition to maintain the undifferentiated growth of hPSCs [8], [9], [26], [27], [38]. In these studies, the pluripotency of hPSCs was confirmed by teratoma and EB formation and analysis of the expression of markers specific to all three germ layers present in these structures.…”
Section: Discussionmentioning
confidence: 99%
“…Line hiPS-31L was derived from human embryonic fi broblasts (culture MAN1) via induction with retroviruses pMX-Oct4, pMX-Sox2 pMX-Klf4, and pMX-c-Myc [1]. We also used human ESC lines HUES9 [8] and hESM04 [12], cell culture obtained from human amniotic fl uid (culture Amn-Fluid2), and partially reprogrammed amniotic fl uid cell line (AF2-r4v4).…”
Section: Methodsmentioning
confidence: 99%
“…We used three strains of human ESC: hESM01, hESM03, and hESM04 [7,8]. The cells were cultured on gelatincoated 35-mm Petri dishes (Costar) using mouse embryonic fi broblasts as the feeder in KODMEM (Invitrogen) containing 20% serum substitute (Invitrogen), 0.1 mM β-mercaptoethanol (Sigma), 1 mM glutamine (Gibco), 1 mM amino acid mixture (Gibco), 4 ng/ml bFGF (Peprotech), and antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription-PCR (RT-PCR) and histoche mical analysis were carried out as described previously [7].…”
Section: Methodsmentioning
confidence: 99%